2015
DOI: 10.1016/j.virol.2015.03.014
|View full text |Cite
|
Sign up to set email alerts
|

Advances in experimental systems to study hepatitis C virus in vitro and in vivo

Abstract: Hepatitis C virus (HCV) represents a global health concern affecting over 185 million people worldwide. Chronic HCV infection causes liver fibrosis and cirrhosis and is the leading indication for liver transplantation. Recent advances in the field of direct-acting antiviral drugs (DAAs) promise a cure for HCV in over 90% of cases that will get access to these expensive treatments. Nevertheless, the lack of a protective vaccine and likely emergence of drug-resistant viral variants call for further studies of HC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
52
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(52 citation statements)
references
References 172 publications
(190 reference statements)
0
52
0
Order By: Relevance
“…Infection with HCV holds a high risk of causing chronic hepatitis, cirrhosis, and hepatocellular carcinoma, resulting in 350,000 human deaths each year. Although current developed direct-acting antivirals (DAAs) are capable of effectively eradicating HCV infection from patients, several hurdles remain, including high costs, emergence of drug resistance, and side effects (2). Treatment with DAAs in a portion of HCV patients suffering from advanced liver disease does not eliminate the risk of hepatocellular carcinoma.…”
mentioning
confidence: 99%
“…Infection with HCV holds a high risk of causing chronic hepatitis, cirrhosis, and hepatocellular carcinoma, resulting in 350,000 human deaths each year. Although current developed direct-acting antivirals (DAAs) are capable of effectively eradicating HCV infection from patients, several hurdles remain, including high costs, emergence of drug resistance, and side effects (2). Treatment with DAAs in a portion of HCV patients suffering from advanced liver disease does not eliminate the risk of hepatocellular carcinoma.…”
mentioning
confidence: 99%
“…Additionally, mutations within Huh-7 cells were identified that improved the ability of the cells to replicate HCV replicons (20,21). The identification of both viral and host cell mutations that allowed for a highly permissive environment would pave the way for the development of replicons representing all HCV genotypes and for the establishment of other cell lines that support HCV replication (22). There was excitement with the establishment of these highly permissible replicon systems; it was initially thought that simply adding back the structural components of the HCV genome would be enough to establish infectious particles.…”
Section: The Long Road Toward Cellbased Systemsmentioning
confidence: 99%
“…Finally, the full life cycle of HCV could be studied, leading to a better understanding of the host and viral factors required for replication and viral entry into host cells (for reviews, see refs. 22,28,29).…”
Section: Selection Under Pressurementioning
confidence: 99%
“…Our insight in the HCV life cycle was hampered for a long time but the development of the HCV pseudoparticle (HCVpp) and HCV cell culture (HCVcc) systems paved the way for a more comprehensive exploration of virus infectivity (Hsu et al, 2003; Wakita et al, 2005). Both systems are now widely used for studying HCV entry and screening for viral inhibitors (Catanese and Dorner, 2015). The envelope proteins E1 and E2 are highly glycosylated membrane-associated proteins consisting of an N-terminal ectodomain and a C-terminal transmembrane domain.…”
Section: Introductionmentioning
confidence: 99%